A cost effectiveness analysis of maintenance cognitive stimulation therapy (MCST) for people with dementia: examining the influence of cognitive ability and living arrangements. (4th May 2019) - Brown, Heather; D'Amico, Francesco; Knapp, Martin; Orrell, Martin; Rehill, Amritpal; Vale, Luke; Robinson, Louise
ABSTRACT: Objectives: Identify if cost-effectiveness of Maintenance Cognitive Simulation Therapy (MCST) differs by type of living arrangement and cognitive ability of the person with dementia. Next, a value of information analysis is performed to inform decisions about future research. Methods: Incremental cost-effectiveness analysis applying seemingly unrelated regressions using data from a multicentre RCT of MCST versus treatment as usual in a population which had already received 7 weeks of CST for dementia (ISRCTN: 26286067). The findings from the cost-effectiveness analysis are used to inform a value of information analysis. Results: The results are dependent upon how quality adjusted life years (QALYs) are measured. MCST might be cost-effective compared to standard treatment for those who live alone and those with higher levels of cognitive functioning. If a further RCT was to be conducted for this sub-group of the population, value of information analysis suggests a total sample of 48 complete cases for both sub-groups would be required for a two-arm trial. The expected net gain of conducting this future research is £920 million. Conclusion: Preliminary results suggest that MCST may be most cost-efficient for people with dementia who live alone and/or who have higher cognition. Future research in this area is needed.